Pengaruh Electronic Word Of Mouth (E-Wom) Dan Cross Selling Terhadap Keputusan Pembelian Produk Erigo. (Studi Kasus Mahasiswa Universitas Islam Malang) - Saputra, Alfito Mauliddani; Wahono, Budi; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze the influence of Electronic Word of Mouth (E-WOM) and Cross Selling strategies on the purchasing decisions of Erigo products among students at Universitas Islam Malang. The research method used is quantitative with a correlational approach. The research sample was selected using purposive sampling techniques, with a total of 60 respondents chosen based on specific criteria. Primary data was collected through questionnaires that had been tested for validity and reliability.The results of the study show that E-WOM has a significant influence on the purchasing decisions of Erigo products, where the more positive the E-WOM, the higher the purchasing decision. Additionally, the Cross Selling strategy was also found to have a positive influence on purchasing decisions, with customers who received additional product offers being more likely to purchase the main product. Overall, the combination of E-WOM and Cross Selling contributes 44.9% to purchasing decisions, while the remaining 55.1% is influenced by other factors not examined in this study. Keywords: Electronic Word of Mouth (E-WOM), Cross Selling, Purchasing Decision, Erigo, Students of Universitas Islam Malang